2020
DOI: 10.1002/cm.21638
|View full text |Cite
|
Sign up to set email alerts
|

Structural change and degradation of cytoskeleton due to the acrolein conjugation with vimentin and actin during brain infarction

Abstract: We have found recently that dendritic spine extension is inhibited through acrolein conjugation with αand β-tubulin proteins during brain infarction. In this current study, we looked for other acrolein-conjugated proteins in the 100,000g precipitate fraction, to clarify how cytoskeleton structure is modified by acrolein. Acroleinconjugated proteins were sought from acrolein-treated mouse FM3A and Neuro2a cells and from tissues isolated from mouse brain infarction. It was found that vimentin was conjugated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…38 This preventive pathway occurs at the expense of reactive oxygen species (ROS) production, as well as of other potential toxic metabolic byproducts, such as acrolein, 39 a highly reactive compound reported to be more toxic than common ROS. 40 Cytotoxic and neurotoxic effects of acrolein have been extensively reported, and high acrolein levels have been proposed to mediate pathological mechanisms underlying brain infarction in mouse models, [41][42][43] as well as blood vessel rupture in cellular models. [44][45][46][47] Elevated levels of acrolein and SSAT have also been detected in the plasma of stroke patients and have been proposed as candidate stroke biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…38 This preventive pathway occurs at the expense of reactive oxygen species (ROS) production, as well as of other potential toxic metabolic byproducts, such as acrolein, 39 a highly reactive compound reported to be more toxic than common ROS. 40 Cytotoxic and neurotoxic effects of acrolein have been extensively reported, and high acrolein levels have been proposed to mediate pathological mechanisms underlying brain infarction in mouse models, [41][42][43] as well as blood vessel rupture in cellular models. [44][45][46][47] Elevated levels of acrolein and SSAT have also been detected in the plasma of stroke patients and have been proposed as candidate stroke biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…36 This preventive pathway occurs at the expense of reactive oxygen species production, as well as of other potential toxic metabolic byproducts, such as acrolein, 37 a highly reactive compound reported to be more toxic than common reactive oxygen species. 38 Cytotoxic and neurotoxic effects of acrolein have been extensively reported, and high acrolein levels have been proposed to mediate pathological mechanisms underlying brain infarction in mouse models, [39][40][41] as well as blood vessel rupture in cellular models. [42][43][44][45] Elevated levels of acrolein and SSAT have also been detected in the plasma of stroke patients, and have been proposed as candidate stroke biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to brain infarction, acrolein also causes tissue damage during dementia, renal failure, and in primary Sjogren's syndrome, possibly through conjugation and modulation of key proteins. Mechanistically, recent studies have shown that acrolein conjugation with tubulins inhibits dendritic spine extension [103], and that acrolein conjugation with vimentin and actin alters the structure of the cytoskeleton following brain infarction [104]. Importantly, levels of protein-conjugated acrolein are a biomarker for risk and severity of these diseases [105].…”
Section: Control Of Polyamine Catabolism and Transportmentioning
confidence: 99%